Parking Fee Disputes: Analysis of Civil Liability of Local Governments and Taxpayers - Syahril, Muh. Akbar Fhad; Hasan, Hamida (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2024)
This research aims to examine the responsibility of parking managers in collecting parking fees in Indonesia from legal and accounting perspectives. The research method used is normative legal research with a statutory approach and a conceptual approach. The results showed that the responsibility of parking managers in collecting parking fees in Indonesia is still not optimal. There are still many problems related to negligence of parking managers, extortion practices, lack of supervision, potential for civil lawsuits, and discrepancies between regional tax regulations and applicable accounting standards. To overcome these problems, a comprehensive effort is needed from various stakeholders, including local governments, law enforcement officials, tax accountants, and parking managers themselves. Strict law enforcement, regulatory harmonization, increased supervision, as well as increased awareness and legal compliance of parking managers are key to realizing the effectiveness of parking fee management in accordance with applicable legal and accounting principles to optimize parking fee revenue as one of the sources of local revenue, as well as to achieve social justice for the community.